Genetics of Uveal Melanoma and Cutaneous Melanoma: Two of a Kind? - Thomas van den Bosch; Emine Kilic; Dion Paridaens; Annelies de Klein (Dermatology Research and Practice)
Cutaneous melanoma and uveal melanoma both derive from melanocytes but show remarkable differences in tumorigenesis, mode of metastatic spread, genetic alterations, and therapeutic response. In this review we discuss the differences and similarities along with the genetic research techniques available and the contribution to our current understanding of melanoma. The several chromosomal aberrations already identified prove to be very strong predictors of decreased survival in CM and UM patients. Especially in UM, where the overall risk of metastasis is high (45%), genetic research might aid clinicians in selecting high-risk patients for future systemic adjuvant therapies.